The Role Of People’s Business Credit (KUR) For Micro, Small And Medium Enterprises (Msmes) In Grobogan Regency - Rizal Ardhiansyah; Rochman Hadi Mustofa (UNIVED Press, 2025)
MSMEs have a significant contribution to the country’s economy, but still experience constraints in capital, so KUR is present as a financing solution in developing MSMEs. This research was conducted in December 2024 – January 2025 to analyze the role of KUR in increasing capital, income and profits of MSMEs in Grobogan Regency. This research used a qualitative method with a case study approach. Data was collected throught interviews and documentation analysis. Interviewees were selected using the snowball sampling method, namely MSME actors. The data was analyzed using the stages: data reduction, data presentation, and conclusion drawing. The results of the research show that KUR contributes to developing business capital, expanding marketing to modern retailers, and increasing MSME tumover and income. In addition, KUR also encourages the creation of new jobs in the MSME sector/ however, challenges such as manual financial records need attention. Thus, the KUR program has provento play a significant role in supporting the growth og MSMEs.